2018
DOI: 10.1108/ijwhm-01-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Do as you say

Abstract: Purpose The purpose of this paper is to uncover the effect of psychosocial safety climate (PSC – a climate for psychological health) on managerial quality and the mediating processes explaining that association. It is posited that the alignment between what is said (espoused PSC) and what is done (enacted PSC via managerial quality) is important for successful organizational interventions. Managers’ own psychosocial work factors act as resources to facilitate the enactment of managerial quality. Design/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
2
25
0
1
Order By: Relevance
“…Research suggests that job autonomy (Biron, 2018;Ohly and Scmitt, 2016), senior management leadership and support (Den Hartog and Belschak, 2016;, and downsizings and mergers influence line managers' proactive work behaviors. This paper adds the line managers' middle-levelness to the list of contextual factors affecting their actions during organizational interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that job autonomy (Biron, 2018;Ohly and Scmitt, 2016), senior management leadership and support (Den Hartog and Belschak, 2016;, and downsizings and mergers influence line managers' proactive work behaviors. This paper adds the line managers' middle-levelness to the list of contextual factors affecting their actions during organizational interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The motivational model of individual-level proactive work behaviors is an appropriate framework for this paper, as line managers were allocated the responsibility for managing the intervention phases. Previous research has found that line managers' autonomy is crucial to achieve the goals of interventions (Biron et al, 2018). Furthermore, job autonomy is crucial for line managers' ability to engage in proactive work behaviors (Ohly and Scmitt, 2016), rendering line managers' middle-levelness and how they manage it a critical factor for the proactive work behaviors they engage in to drive the intervention -or not.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from confirmatory factor analyses support the construct validity of the theoretically based four-factor structure measured by the 12-item version of PSC (Hall et al, 2010;Pien et al, 2018). Despite the theoretical reasoning behind the PSC measure, it seems data most often are collapsed into one single composite PSC score (see e.g., Afsharian et al, 2018;Biron et al, 2018;Bronkhorst, 2015;Idris et al, 2015;Potter et al, 2017). In addition, a 4-item version comprising the theoretical dimensions has been introduced (Dollard & Bakker, 2010).…”
Section: Length and Format Of The Psc Instrumentmentioning
confidence: 83%
“…The PSC comprises four theoretically based components: how employees perceive the senior management 1) engages, 2) prioritizes, 3) communicates, and 4) involves employees in psychosocial workplace safety issues (Dollard & Bakker, 2010). PSC has been found to be a useful indicator for examining how policies and procedures at the organizational level affect employees' health and well-being (Bakker & van Woerkom, 2018;Biron et al, 2018).…”
Section: Psychosocial Safety Climate In Organizationsmentioning
confidence: 99%
See 1 more Smart Citation